Karyology and Genome Size Analyses of Iranian Endemic Pimpinella (Apiaceae) Species - Mehravi, Shaghayegh; Ranjbar, Gholam Ali; Najafi-Zarrini, Hamid; Mirzaghaderi, Ghader; Hanifei, Mehrdad; Severn-Ellis, Anita Alice; Edwards, David; Batley, Jacqueline (Frontiers in Plant Science, 2022)
Pimpinella species are annual, biennial or perennial semi-bushy aromatic plants cultivated for folk medicine, pharmaceuticals, food and as spices. The karyology and genome size of 17 populations of 16 different Pimpinella species, collected from different locations of Iran, were analyzed for inter-specific karyotypic and genome size variations. For karyological studies, root tips were squashed and painted with aceto-orcein 1% (w/v). For flow cytometric (FCM) measurements, fresh leaves of the standard reference (Solanum lycopersicum cv. Stupick, 2C DNA = 1.96 pg) and the Pimpinella samples were stained with propidium iodide (PI). There were two ploidy levels identified: diploid (2x) and tetraploid (4x), as well as five metaphase chromosomal counts of 18, 20, 22, 24, and 40. The 2n = 24 is reported for the first time in the Pimpinella genus and the presence of a B-chromosome is reported for one species. The nuclear DNA contents ranged from 2C = 2.48 to 2C = 5.50 pg, along with a wide range of genome size between 1212.72-2689.50 Mbp. The average monoploid genome size and average value of 2C DNA/chromosome were not proportional to ploidy. There were considerable positive correlations between 2C DNA and total chromatin length (X) and total chromosomal volume (TCV). The results of the present study enable us to classify the genus Pimpinella, which has high morphological variation in Iran. In addition, cytological studies demonstrate karyotypic differences between P. anthriscoides and other species of Pimpinella, which may be utilized as a novel identification key to affiliate into a distinct, new genus Pseudopimpinella.